Development Of The Potential Of Perancak Beach As An Ecotourism-Based Tourism Destination In Jembrana - Dwi Candra Anggara, I Gusti Made; Wulandari, Pande Putu; Darma Susila, I Made Gede (Politeknik Internasional Bali, 2024)
Perancak Beach is a tourist attraction located in Perancak Village, Jembrana Regency, which has been designated as a tourist attraction in Jembrana Regency. One of the main attractions at this tourist attraction tends to be nature tourism and education regarding turtle conservation. This research identifies the conservation-based potential development of Perancak Beach in Jembrana Regency. This research aims to identify existing potential and obtain strategy recommendations in efforts to develop conservation-based tourism potential at Perancak Beach, Jembrana Regency. This research uses a descriptive approach with qualitative data types. The data collection techniques used were observation, interviews, and literature study. The data analysis technique used is descriptive analysis. The research results show that the tourism potential of Perancak Beach is supported by 4 adequate destination components and a conservation-based destination development strategy using the concept of ecotourism (environmental planning and management, increasing environmental awareness and protection, and institutional regulations).